PENGARUH COMPUTER ATTITUDE, COMPUTER SELF EFFICACY, DAN TRUST TERHADAP MINAT MENGGUNAKAN SOFTWARE AKUNTANSI PADA KARYAWAN LPD SE-KOTA DENPASAR - I Nyoman Rasmen Adi; Putu Eka Purnama Yanti (Universitas Pendidikan Nasional, 2018)
The Influence of Computer Attitude, Computer Self Efficacy, and Trust on the Interest of Using Accounting Software at LPD in Denpasar. Denpasar City is one of city in Bali that still makes the LPD (Lembaga Perkreditan Desa) a business entity that can improve people’s welfare. Denpasar City’s LPD is a financial institution that utilizes accounting software in processing data and transactions. The use of accounting software in the Denpasar City’s LPD is very operational in accommodating all information and producing reports quickly and accurately so that they can be useful in decision making. This study aims to determine the effect of whether Computer Attitude, Computer Self Efficacy, and Trust towards the Interest Using Accounting Software. The theory used in this study is the theory of Technology Acceptance Model (TAM). This study was carried out in all LPD in the city of Denpasar. The population in this study were employees who using accounting software. Based on the population, sample were selected through simple random sampling, while 60 employees taken as sample by using of formula Slovin. The data collected by documentation and questionnaires. The data analysis technique used are descriptive statistics and multiple linear regression analysis. The results of this study are: 1) computer attitude do not have impact on interest using accounting software. 2) computer self efficacy has a positive and significant impact on the interest using accounting software 3) trust has a positive and significant impact on the interest using accounting software. 4) computer attitude, computer self efficacy, and trust have a positive and significant impact simultaneously on the interest using accounting software.Keywords: Computer attitude, computer self efficacy, trust, and the interest of using accounting software